Laparoscopic versus open complete mesocolic excision with central vascular ligation in right colon cancer - El-Fol, Hossam Abdelkader; Ammar, Mohamed Sabry; Abdelaziz, Tamer Fakhry; Elbalshy, Mohammed A.; Elabassy, Mahmoud M. (International Surgery Journal, 2019)
Background: The purpose of this study was to compare between laparoscopic and open complete mesocolic excision (CME) with central vascular ligation (CVL) in right colon cancer. Methods: From January 2016 to December 2018, a prospective cohort study of 60 patients who diagnosed as operable right sided colon cancer was performed. The patients were classified into laparoscopic CME with CVL and open CME with CVL groups. Demographic variables, comorbidities, tumor location, intraoperative parameters, duration of hospital study, histopathological findings, postoperative complications and follow up data were compared between the two groups. Demographic variables included age and sex distribution. Intraoperative parameters included incision length, operative time and operative blood loss. Results: 60 patients were selected in this study. Both groups were the same in the age and sex distribution, potential comorbidities and tumor location. Patients in the Laparoscopic CME with CVL group had shorter incision lengths, longer operative times, less operative blood loss, shorter hospital stay, less number of retrieved lymph nodes , the same TNM (tumor nodes metastasis) classifications, similar histopathological findings and comparable incidence of postoperative complications. Conclusions: Laparoscopic CME with CVL procedure is a safe, valid and feasible surgical method for right colon cancers.